2020
DOI: 10.1016/j.bbi.2020.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Creutzfeldt-Jakob disease in a man with COVID-19: SARS-CoV-2-accelerated neurodegeneration?

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 15 publications
5
82
0
Order By: Relevance
“…He died 2 months after onset. Examinations of EEG, MRI, CSF RT-QuIC, CSF 14-3-3, and tau protein highly indicated the diagnosis of sporadic CJD (sCJD) (Young et al, 2020). He displayed a fast progression and a short duration compared with majority of sCJD patients (Young et al, 2020).…”
Section: Covid-19 and Prion Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…He died 2 months after onset. Examinations of EEG, MRI, CSF RT-QuIC, CSF 14-3-3, and tau protein highly indicated the diagnosis of sporadic CJD (sCJD) (Young et al, 2020). He displayed a fast progression and a short duration compared with majority of sCJD patients (Young et al, 2020).…”
Section: Covid-19 and Prion Diseasementioning
confidence: 99%
“…Examinations of EEG, MRI, CSF RT-QuIC, CSF 14-3-3, and tau protein highly indicated the diagnosis of sporadic CJD (sCJD) (Young et al, 2020). He displayed a fast progression and a short duration compared with majority of sCJD patients (Young et al, 2020). It has been noticed that COVID-19 can sometimes trigger unspecific inflammatory in CNS (Ellul et al, 2020;Pan et al, 2020;Paterson et al, 2020).…”
Section: Covid-19 and Prion Diseasementioning
confidence: 99%
“…Patients with polyradiculoneuritis and cranial neuritis have also been described [ 25 ]. Rare cases of acute Parkinsonism and a single case of Creutzfeldt Jacob syndrome has been reported [ 26 ]. It remains unknown if other neurodegenerative diseases can be precipitated by this infection.…”
Section: Post-viral Complicationsmentioning
confidence: 99%
“…A recent case report of a > 60-year-old patient reported that the onset of clinical sCJD signs occurred concurrently with those of COVID-19 [ 250 ]. Further studies are clearly necessary to investigate this association, and coincidence cannot be entirely excluded.…”
Section: Cns Prion Diseasementioning
confidence: 99%